P423 Effect of tofacitinib on colectomy risk in anti TNF-alfa refractory ulcerative colitis. (30th January 2023) - Romeo, S; Carvalhas Gabrielli, A M; Ferretti, F; Piazza O Sed, N; Mazzola, A M; Alicante, S; Berté, R; Scribano, M L; Buscarini, E; Ricci, C; Caprioli, F; Ardizzone, S; et al.
Abstract: Background: Tofacitinib is an oral janus kinase inhibitor (JAK) approved for patients with moderate to severe ulcerative colitis (UC) and either inadequate response or loss of response or intolerance to conventional or biologic therapy. The 5-year and 10-year cumulative risk of colectomy in UC is 10%–15%. 1 Due to the increasing number of anti tumor necrosis factor (TNF)-alfa non responders, tofacitinib seems a valuable therapeutic alternative. This study aims to assess the effectiveness of tofacitinib in preventing colectomy in patients with moderate-to-severe UC refractory to anti TNF-alfa agents. Methods: We performed an observational retrospective and prospective multicenter study in five Italian IBD referral units including adult patients with confirmed diagnosis of moderate-to-severe UC (defined by a total Mayo score ≥ 6), treated with tofacitinib because of response failure or intolerance to anti TNF-alfa agents. Primary aim was the effectiveness of tofacitinib in preventing colectomy during a follow-up of 52 weeks. Secondary aims were: survival without colectomy, survival without tofacitinib discontinuation, clinical remission (defined as Mayo partial score ≤ 2) at week 8, 24 and 52, endoscopic remission (defined as Mayo endoscopic score ≤ 1) and steroid-free clinical remission (Mayo Partial score ≤ 2 without steroid) at week 52; adverse events (AE) to tofacitinib. Descriptive statistics and Kaplan Meier analyses of survival were performed. Results: From January 2021 to October 2022 45 patients were included. During the follow-up, 6 patients (13%) underwent colectomy and all of them before week 24. Survival without colectomy and survival without tofacitinib discontinuation are represented in Figs.1-2. Clinical remission was reached by 17 patients (37.7%) at week 8, by 20 (44.4%) at week 24, and by 22 patients (48.8%) at week 52. Among the 11 patients with an endoscopic evaluation available after completing 52-week treatment, 9 (82%) achieved endoscopic remission. At week 52, 22 patients (49%) maintained steroid-free clinical remission. In eighteen patients (40%) tofacitinib was interrupted, because of failure in 15 and because of a severe AE in 3. AE occurred in 9 patients (20%), but in 3 only (6.7%) were severe and entailed treatment interruption. Conclusion: These data confirm effectiveness and safety of tofacitinib in preventing colectomy in moderate-to-severe UC refractory to anti TNF-alfa agents.